Recent developments in the world of open access, open data, and open education - Hall, Robyn; Abbott, Meghan (My University, 2015)
A dynamic, global community of academics and students are working to advance Open Access, Open Data, and Open Education. Come learn more about these efforts as well as opportunities open to faculty here at MacEwan interested in reshaping education and research to be more equitable, inclusive, and sustainable.
Presented on December 3, 2015 at the Centre for the Advancement of Faculty Excellence (CAFE) at MacEwan University in Edmonton, Alberta.
Keywords: open access; open data; open education resources; research mandates; Tri-Council; open science